Antibacterial properties of herbal denture cleanser based on Graptophyllum pictum L. Griff. leaves - Nadia Kartikasari; Ratri Maya Sitalaksmi; Muhammad Rafi Nurfaiz Arifin; Aurelia Della Imani; Agus Dahlan; Harry Laksono; Aisyah Rachmadani Putri Gofur (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Removable partial dentures (RPDs) are one therapeutic option for tooth loss replacement. Despite its high absorption and porous qualities, acrylic resin—which is frequently used as the base material for RPDs—may encourage the growth of microorganisms and the development of plaque. Graptophyllum pictum L. Griff (G. pictum) has been commonly used in herbal medicine due to its pharmacological effects, which include immunomodulatory, antioxidant, anti-inflammatory, antibacterial, and antifungal activities. Purpose: This study aims to assess the antibacterial properties of an herbal denture cleanser based on G. pictum in effervescent granule against Porphyromonas gingivalis (Pg) and Aggregatibacter actinomycetemcomitans (Aa). Methods: The antibacterial activity was examined using the spread plate method at different time points. The number of Aa and Pg bacteria was determined using colony-forming units (CFUs) and bactericidal ratio (BR%). The statistical analysis employed the Kruskal–Wallis and post-hoc Mann–Whitney U tests (P < 0.05). Results: The results indicate that the herbal cleanser’s antibacterial effectiveness against Aa and Pg increased significantly over time, reaching its optimal level after a 15-minute soaking period, as evidenced by the CFUs and BR%. Conclusion: The herbal denture cleanser based on G. pictum demonstrated antibacterial properties against Pg and Aa, which are significant pathogens in oral infections. These results indicate that this herbal formulation has potential as an effective alternative for future denture cleaning applications.